Upaya Guru Bimbingan Konseling Memberikan Pemahaman Fungsi Bimbingan Konseling Pada Siswa Di SMA Katolik Karitas Tomohon - Langi, Tamara S.; Sundah, Ariantje J. A. (Jurnal Ilmiah Wahana Pendidikan, 2023)
Failure to understand the guidance and counseling service program triggers the service not operating properly. This expo-facto qualitative research reveals that services are carried out in schools with the aim of describing the efforts of guidance and counseling teachers to provide students with a proper understanding of function and meaning. Class XII S students were the main research location to gain a correct understanding of the function and meaning of the guidance and counseling service program at school. So that students change their perception of guidance and counseling teachers, who initially saw guidance and counseling teachers as school police, who would charge various types of charges. Guidance teacher. the school principal, and several students were the main informants in this research regarding perceptions and/or understanding as well as the implementation and guidance and counseling services in schools. Data collection was carried out through interviews, documentation and observation methods. The guidance and counseling teacher who has just been placed at the high school has started carrying out his duties by carrying out a needs analysis (needs assessment). The first program provides an understanding of the function and meaning of guidance and counseling services in schools. This service succeeded in changing the perception of students who saw guidance and counseling teachers as school police. In implementing guidance and counseling, guidance and counseling teachers are also supported by the school principal with very limited facilities. Guidance and counseling services are carried out by one BK teacher with a total of around 800 students. This shows an imbalance between guidance and counseling teachers and the number of students who must be served, so that services are often only carried out in group and classical forms. Through the results of this research, several suggestions can be given: (1) facilities need to be paid attention to in order to provide them completely. (2) It is very necessary to add 4 guidance and counseling teachers so that guidance and counseling services can cover all students. (5) BK teachers need to establish good collaboration with each guardian teacher, and also subject teachers as a source of information regarding students' progress in lessons.